Gene silencing in microalgae: Mechanisms and biological roles. (May 2015) - Kim, Eun-Jeong; Ma, Xinrong; Cerutti, Heriberto
Highlights: Most Archaeplastida microalgae contain histone H3 lysine 27 methyltransferase genes. Pervasive DNA cytosine methylation seems to rely on diverged DNA methyltransferases. RNA interference mechanisms, when present, may suppress transposons and viruses. The role of epigenetic silencing mechanisms in gene regulation remains uncharacterized. RNA interference is a useful tool for functional analyses and genetic engineering. Abstract: Microalgae exhibit enormous diversity and can potentially contribute to the production of biofuels and high value compounds. However, for most species, our knowledge of their physiology, metabolism, and gene regulation is fairly limited. In eukaryotes, gene silencing mechanisms play important roles in both the reversible repression of genes that are required only in certain contexts and the suppression of genome invaders such at transposons. The recent sequencing of several algal genomes is providing insights into the complexity of these mechanisms in microalgae. Collectively, glaucophyte, red, and green microalgae contain the machineries involved in repressive histone H3 lysine methylation, DNA cytosine methylation, and RNA interference. However, individual species often only have subsets of these gene silencing mechanisms. Moreover, current evidence suggests that algal silencing systems function in transposon and transgene repression but their role(s) in gene regulation or other cellular processes remains virtually unexplored, hindering rational genetic engineering efforts.